Prolonged Exposure of CBA/Ca Mice to Moderately Loud Noise Can Cause Cochlear Synaptopathy but Not Tinnitus or Hyperacusis as Assessed With the Acoustic Startle Reflex. (March 2018) - Pienkowski, Martin
Hearing loss changes the auditory brain, sometimes maladaptively. When deprived of cochlear input, central auditory neurons become more active spontaneously and begin to respond more strongly and synchronously to better preserved sound frequencies. This spontaneous and sound-evoked central hyperactivity has been postulated to trigger tinnitus and hyperacusis, respectively. Localized hyperactivity has also been observed after long-term exposure to noise levels that do not damage the cochlea. Adult animals exposed to bands of nondamaging noise exhibited suppressed spontaneous and sound-evoked activity in the area of primary auditory cortex (A1) stimulated by the exposure band but had increased spontaneous and evoked activity in neighboring A1 areas. We hypothesized that the cortically suppressed frequencies should for some time after exposure be perceived as less loud than before (hypoacusis), whereas the hyperactivity outside of the exposure band might lead to frequency-specific hyperacusis or tinnitus. To investigate this, adult CBA/Ca mice were exposed for >2 months to 8 to 16 kHz noise at 70 or 75 dB sound pressure level and tested for hypo-/hyperacusis and tinnitus using tone and gap prepulse inhibition of the acoustic startle reflex. Auditory brainstem responses and distortion product otoacoustic emissions showed evidence of cochlear synaptopathy after exposure at 75 but not 70 dB, putting a lower bound on damaging noise levels for CBA/Ca mice. Contrary to hypothesis, neither exposure significantly shifted startle results from baseline. These negative findings nevertheless have implications for startle test methodology and for the putative role of central hyperactivity in hyperacusis and tinnitus.